REDESIGN GEOMETRIK RUAS JALAN RAYA EMPLAK KALIPUCANG KABUPATEN PANGANDARAN: (КМ 202,5 - КМ 203,5) - Nurul hakim, Luthfi; Saepudin, Uu; Defiana, Yanti (Jurnal Ilmiah Teknik Sipil, 2026)
This study aims to evaluate the existing geometric conditions of the Emplak-Kalipucang road segment in Pangandaran Regency, which has not fully met the required standards of driving comfort and safety. variation in topography and the presence of curves with inadequate radii potentially reduce the performance and safety of the roadway. Therefore, a detailed geometric redesign analysis is required to improve the service quality and operational performance of this road segment. The research methodology involved field contour measurements using a Total Station at several observation points, which were then processed into contour maps as the basis for determining the horizontal and vertical alignments. The geometric analysis was conducted in accordance with the Geometric Design Guidelines for Roads (Guideline No. 13/P/BM/2021) and the Regulation of the Minister of Public Works and Housing No. 19/PRTM/2011. The redesigned alignment resulted in four curves comprising Spiral-Circle-Spiral (SCS) and Spiral-Spiral (SS) types, each with different radii and intersection angles, requiring adjustments to satisfy the design speed of 40 km/h. Additionally, cut and fill areas were calculated to adjust the road elevation according to the redesigned geometric profile. The results indicate that cut and fill works are necessary to achieve a safe and comfortable roadway alignment. Overall, the geometric redesign produced in this study is expected to enhance safety, efficiency, and traffic flow along the Emplak-Kalipucang road section, as well as serve as a reference for construction planning and field supervision.